PENGEMBANGAN CITRA WILAYAH PERBATASAN INDONESIA–MALAYSIA SEBAGAI PUSAT EKONOMI DAN PARIWISATA LINTAS BATAS - Melyana R Pugu (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to analyze the development of the image of the Indonesia–Malaysia border region as a center for cross-border economic and tourism activities. Border areas are no longer viewed merely as administrative and security zones, but also as strategic spaces for economic growth, cultural interaction, tourism development, and bilateral cooperation. This study uses a qualitative descriptive approach with a library research method. Data were obtained from secondary sources, including scientific journal articles, books, policy documents, institutional reports, and relevant previous studies. The analysis was conducted through literature selection, thematic classification, content analysis, and conceptual synthesis. The findings show that the Indonesia–Malaysia border region has strong potential through cross-border trade, cultural proximity, natural attractions, local communities, micro, small, and medium enterprises, and border infrastructure. However, this potential has not been optimally transformed into a strong regional image due to limited promotion, infrastructure gaps, weak destination governance, and the persistent perception of border areas as peripheral regions. Therefore, regional image development needs to be integrated with destination branding, regional branding, infrastructure improvement, local community empowerment, tourism product development, and cross-border institutional cooperation. The study concludes that the Indonesia–Malaysia border region can be positioned as a competitive cross-border economic and tourism hub if its image is developed consistently based on local identity, accessibility, service quality, and Indonesia–Malaysia collaboration.